2016
DOI: 10.1371/journal.pone.0167781
|View full text |Cite|
|
Sign up to set email alerts
|

Discovering SIFIs in Interbank Communities

Abstract: This paper proposes a new methodology based on non-negative matrix factorization to detect communities and to identify central nodes in a network as well as within communities. The method is specifically designed for directed weighted networks and, consequently, it has been applied to the interbank network derived from the e-MID interbank market. In an interbank network indeed links are directed, representing flows of funds between lenders and borrowers. Besides distinguishing between Systemically Important Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Given the high correlation of both TFP and Net Worth with their own lags and given that our model is static, we run the following specification: Export i,t = α + β 0 T F P i, t + β 1 N etW orth i,t + β 3 P AV IT T + e i,t (37) where Pavitt is the well-known Pavitt's taxonomy, which distinguish between supplierdominated, scale-intensitive, specialized suppliers and science-based firms. As mentioned above, we do not intend to study any causal effect between the variables but only the existence of the correlations emerged from the theoretical framework.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Given the high correlation of both TFP and Net Worth with their own lags and given that our model is static, we run the following specification: Export i,t = α + β 0 T F P i, t + β 1 N etW orth i,t + β 3 P AV IT T + e i,t (37) where Pavitt is the well-known Pavitt's taxonomy, which distinguish between supplierdominated, scale-intensitive, specialized suppliers and science-based firms. As mentioned above, we do not intend to study any causal effect between the variables but only the existence of the correlations emerged from the theoretical framework.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Moreover, since several studies have found the presence of sets of very dense sub-graphs, with few connections between them, as a result of similar patterns at the micro-level (see Pecora et al, 2016 ; Spelta et al, 2018 ), we also apply the Louvain Method to extract the community structure of the network (see Blondel et al, 2008 ). The identified communities maximize system's modularity, a measure that quantifies the strength of the division of the system into communities of densely interconnected nodes that are only sparsely connected with the rest of the system (see Newman, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…VOACAP is written in Fortran and appears to be the natural evolution of IONCAP (Ionospheric Communications Analysis Prediction), inheriting from the latter the entire theoretical basis. 37 This software was originally designed for Voice of America (the official broadcasting service of the Federal Government of the United States, supervised by the Broadcasting Board of Governors), and today is considered "the most professional HF system performance prediction tool available on the market" (www.voacap.com). 38 In order to be able to have an automated procedure to obtain the required output data, we had two engineers developing a custom software interface (Radio Propagation And Data Aggregation -RadioPropagAnDA)…”
Section: Appendix a Sky-wave Signal Predictionmentioning
confidence: 99%
“…The program provides a prediction of radio signal strength in terms of Signal-to-Noise Ratio (SNR) for each BBC transmitter-frequency-power combination, in each Italian municipality in each month and in each half-an-hour range. We then average out the 37 www.voacap.com/documents/familychart.pdf. 38 See also www.met.nps.edu/~psguest/EMEO_online/module3.…”
Section: Appendix a Sky-wave Signal Predictionmentioning
confidence: 99%